Complete genome sequence of the sulfate-reducing firmicute Desulfotomaculum ruminis type strain (DLT). Issue 2 (September 2012) - Spring, Stefan; Visser, Michael; Lu, Megan; Copeland, Alex; Lapidus, Alla; Lucas, Susan; Cheng, Jan-Fang; Han, Cliff; Tapia, Roxanne; Goodwin, Lynne; Pitluck, Sam; Ivanova, Natalia; et al.
Abstract Desulfotomaculum ruminis Campbell and Postgate 1965 is a member of the large genusDesulfotomaculum which contains 30 species and is contained in the familyPeptococcaceae . This species is of interest because it represents one of the few sulfate-reducing bacteria that have been isolated from the rumen. Here we describe the features ofD. ruminis together with the complete genome sequence and annotation. The 3, 969, 014 bp long chromosome with a total of 3, 901 protein-coding and 85 RNA genes is the second completed genome sequence of a type strain of the genusDesulfotomaculum to be published, and was sequenced as part of the DOE Joint Genome Institute Community Sequencing Program 2009.